Growing Synergy between the Knowledge Society and Cognitive Translation Studies - Bohatyrets, Valentyna; Kudelko, Zoya; Melnychuk, Liubov (Universitatea "Ştefan cel Mare" din Suceava, 2021)
Remarkably, in the era of disruptive innovation, rapid technological change, ubiquitous connectivity, machine learning, and algorithmic governance, cognitive translation is undergoing a period of innovative drastic transformation. A ‘now generation’ of digital natives appears to dominate every walk of human life. The impact of digital technology and the World Wide Web on translation is incessant, all-encompassing and insightful. Furthermore, the emergence of cognitive translation studies has stipulated an interdisciplinary approach to delve into the cognitive and behavioral aspects of a broad array of cross-language activities including all kinds of translation and interpreting, namely, such issues as bilingualism and second language acquisition represent in many ways an even tighter focus on the uniquely human elements of linguistic structure and function, as theories build on and remain linked to current and developing knowledge of human cognitive processes. This paper outlines why Cognitive Translation Studies has become the pivotal focus of scientists, academia and students’ activities ; what is supposed to be done to stir a greater interest toward the problem of integrating TS among critical communication of scholars, and to encourage further theoretical and empirical engagements with this phenomenon. What is cognitive translation in the context of language teaching and learning? What could be the perception of English speaking EFL teachers regarding the introduction of translation‐based activities in their classroom practices? How could the implementation of translation activities within the language classroom improve learners’ cognitive skills? In order to investigate the perceived students’ cognitive and performance problems in the translation-based learning, we resorted to a questionnaire, which aimed for “concrete and complex illustrations” and, accordingly, provided the students with opportunities to consider their own experiences and give their feedback in terms of the impact of technology on translators and interpreters as well as in terms of developing their cognitive skills
Keywords: cognitive translation studies,; knowledge society; synergy; high-quality translation; Department of Modern Foreign Languages & Translation Studies; interdisciplinarity